Critical Distance - Critical Distance (Critical Distance)
Back in 2009, Critical Distance was founded to answer the question: “Where is all the good writing about games?” Our goal for the last 10 years has always been to facilitate dialogue. Through roundups, roundtables, podcasts, and critical compilations, we provide one place where all the most important discourse is collected together. We aim to build a foundation for ongoing conversations between developers, critics, educators and enthusiasts about critical issues in games culture. We are a compendium of the most incisive, thought-provoking, and remarkable discussion in and around games, keeping it archived for years to come. Our work has helped new writers to find their voice, educators to find resources to help their students develop critical thinking, and developers to become more reflective in their design practice.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 2-Étude des représentations; 5-Auteur.rice PANDC; _Nettoyé